Peran Kebijakan Pemerintah Dalam Mendorong Green Economy Dalam Meningkatkan Kesadaran Manfaat Kendaraan Listrik - Arief Teguh Nugraha; Surya Bintarti; Yuhaning Praborini (JPIES: Jurnal Pelita Ilmu Ekonomi Syariah, 2025)
Climate change and air pollution are driving the Indonesian government to transform the transportation sector towards more environmentally friendly mobility, this government policy encourages the implementation of a green economy. The paradigm of the green economy from the community methodologically, conceptualization, implementation, and criticism leads to the challenges of global strategies that have the goals of sustainability, poverty alleviation, and inclusion of vulnerable social sectors. The purpose of this study is to see the influence of government policies in encouraging a green economy to increase awareness in using electric vehicles. The research method used is descriptive qualitative with data collection techniques using literature studies. The results of the study indicate that government policies in encouraging a green economy are able to encourage the use of electric vehicles in Indonesia has developed and has benefits for environmental sustainability, such as reducing air pollution. Electric vehicles also encourage the program to achieve a green economy in Indonesia.